Clinical and Echocardiographic Outcomes After Aortic Valve Repair Surgery. Issue 3 (June 2019) - Ram, Eilon; Orlov, Boris; Shinfeld, Ami; Kogan, Alexander; Sternik, Leonid; Raanani, Ehud
Objective: To assess early and late clinical outcomes in patients who underwent aortic valve repair surgery for aortic valve insufficiency, and to investigate predictors for recurrence. Methods: Of 151 consecutive patients who underwent aortic valve repair surgery for varying degrees of aortic insufficiency (AI) in our department between 2004 and 2018, 60 (40%) underwent aortic root replacement, 71 (47%) aortic cusp plication, 31 (20%) subcommissural annuloplasty, 29 (19%) circular annuloplasty, and 28 (18%) autologous pericardial patch augmentation. Results: One patient died in the hospital (0.7%). Mean clinical and echocardiographic follow-up was 62±43 months (range 1 to 159) and 50 ± 40 months (range 1 to 158), respectively. The overall survival rate was 99.3% at 1 year and 98% at 5 years of follow-up. Seventeen patients (11.3%) had recurrent severe AI, and all of them underwent reoperation with a mean duration to reoperation of 35 ± 39 months. Risk factors for the development of recurrent significant AI (≥3) or reoperation, by univariable analysis, were unicuspid or bicuspid aortic valve (AV) ( P = 0.018), the use of subcommissural annuloplasty ( P = 0.010), the need for cusp repair ( P = 0.001), and the use of pericardial patch augmentation ( P < 0.001). By multivariable analysis only the use of pericardial patch augmentation emerged as a significant independent predictor for the development of recurrent significant AI (≥3) or reoperation ( P = 0.020). Conclusion: AV repair can be performed with low morbidity and mortality, with good early and late clinical outcomes. However, in our experience there was a significant rate of recurrent AI especially in patients who underwent cusp augmentation using glutaraldehyde-treated autologous pericardial patch.